2014
DOI: 10.3390/su6107466
|View full text |Cite
|
Sign up to set email alerts
|

A Site Selection Model for a Straw-Based Power Generation Plant with CO2 Emissions

Abstract: Abstract:The decision on the location of a straw-based power generation plant has a great influence on the plant's operation and performance. This study explores traditional theories for site selection. Using integer programming, the study optimizes the economic and carbon emission outcomes of straw-based power generation as two objectives, with the supply and demand of straw as constraints. It provides a multi-objective mixed-integer programming model to solve the site selection problem for a straw-based powe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 16 publications
0
6
0
Order By: Relevance
“…A multi-objective mixed-integer programming model is introduced to solve the site selection problem for a straw-based power generation plant [6]. Using integer programming, the study optimizes two objectives of the economic and environmental outcomes of straw-based power generation, with the supply and demand of straw as constraints.…”
Section: Methodologies Of Sustainability Sciencementioning
confidence: 99%
See 2 more Smart Citations
“…A multi-objective mixed-integer programming model is introduced to solve the site selection problem for a straw-based power generation plant [6]. Using integer programming, the study optimizes two objectives of the economic and environmental outcomes of straw-based power generation, with the supply and demand of straw as constraints.…”
Section: Methodologies Of Sustainability Sciencementioning
confidence: 99%
“…Without a sufficient straw supply, the plant's performance may be quite poor, resulting in lower economic benefit and higher carbon emissions. Thus, using a linear multi-objective integer program model, the research found that the straw acquisition range could be a determining factor for the straw-based power generation plant's performance [6]. New challenges from nuclear power plants present another issue on the power generation front.…”
Section: Important Issues For a Sustainable Asiamentioning
confidence: 99%
See 1 more Smart Citation
“…When doing this, the local authority considers the site requirements, community impact, environmental impact, health impact and economic impact for the sustainable development of the plant and the region [13]. At the same time, the CPP owner attempts to interact with the local authority to ensure profit maximization.…”
Section: Phase Ii: Modelling Technique For Ranking the Alternative Simentioning
confidence: 99%
“…The GIS technique is applied here to identify the potential feasible sites based on existing information (such as the geology, available power networks and fuel supplies) as this technique has been widely used to identify sites for predetermined construction projects [9][10][11]. Ranking the alternative sites and selecting the most suitable sites are difficult as they depend on many impact factors, all of which need to be identified based on comprehensive field investigations and surveys [12,13].…”
Section: Introductionmentioning
confidence: 99%